On the concept of freedom: freedom's relation to ethics and an application of a Collingwoodian framework - Stoncius, Alec, author; Rollin, Bernard, advisor; Gorin, Moti, advisor; Hamid, Idris, committee member; Delahunty, Gerald, committee member (Colorado State University. Libraries, 2019)
In this project, I will begin by exploring the conceptual relations to the concept of free will, namely the relation of ethics. I will argue that any conception of normative ethics is dependent on a conception of free will and free action. Beginning with this section, it is my hope to convince the reader that the free-will debate has genuine stakes, and providing an account of free will is necessary to the preservation of ethics. The second half will be an attempt to preserve the concept of ethics by articulating a theory of free will that uses the metaphysics of R.G. Collingwood. The application of Collingwood's metaphysics begins with the phenomenology of concepts as the foundation for thought, and seeks to develop these concepts through a scale of forms. The purpose for this application is to overcome the antinomy of the free-will debate by reconciling opposing concepts (i.e. "freedom" and "determinism") into one landscape of understanding.